Large herbivores limit CO 2 uptake and suppress carbon cycle responses to warming in W est G reenland - Sean M. P. Cahoon; Patrick F. Sullivan; Eric Post; Jeffrey M. Welker (Global Change Biology, 2012)
Changes in the terrestrial carbon cycle may ameliorate or exacerbate future climatic warming. Research on this topic has focused almost exclusively on abiotic drivers, whereas biotic factors, including trophic interactions, have received comparatively little attention. We quantified the singular and interactive effects of herbivore exclusion and simulated warming on ecosystem CO 2 exchange over two consecutive growing seasons in W est G reenland. Exclusion of caribou and muskoxen over the past 8 years has led to dramatic increases in shrub cover, leaf area, ecosystem photosynthesis, and a nearly threefold increase in net C uptake. These responses were accentuated by warming, but only in the absence of herbivores. Carbon cycle responses to herbivore exclusion alone and combined with warming were driven by changes in gross ecosystem photosynthesis, as limited differences in ecosystem respiration were observed. Our results show that large herbivores can be of critical importance as mediators of arctic ecosystem responses to climate change.